Chapter Юмор и ирония как средства борьбы с атеизмом в дискурсе Ф.М. Достоевского - Aloe, Stefano (Biblioteca di Studi Slavistici, 2023)
Humor and Irony as a Means of Combating Atheism in the Discourse of F.M. Dostoevsky . The question of the God's existence troubled Dostoevsky throughout his life. He created a very convincing portrait of the atheist of his time. He did not consider unbelievers immoral, but only "infected with recklessness", and when speaking of his atheist acquaintances, often admitted that they were good people. Dostoevsky created the image of an atheist as an intelligent person, who is guided not by the heart, but by the mind and who often evokes sympathy for his questing, his thinking, and his suffering (like Versilov or Ivan Karamazov). If we carefully consider the "atheistic" characters of Dostoevsky, however, we will see that atheism is a phenomenon associated with something both bad and funny. Through humorous details, Dostoevsky imperceptibly creates an image of the "atheist" as a comical and frivolous person.